Stimulus-dependent amygdala involvement in affective theory of mind generation - Schmitgen, Mike; Schnell, Knut (NeuroImage, 2016)
Successful social interaction requires knowledge about another person's emotional states, represented in an affective theory of mind (ToM). This information can be acquired either directly or indirectly, i.e., by observing emotional facial expressions (EFE) or indirectly by inferring emotions through cognitive perspective taking. Therefore, it is of great interest how the function of the cortical ToM network and the limbic system in affective ToM depends on the presence of facial expressions. We addressed this question in a functional magnetic resonance imaging (fMRI) study. The experimental paradigm applied a well-established ToM cartoon task to test functional effects of EFE on the activation of the amygdala and the anterior ToM network during affective ToM judgments. During the task, 22 healthy participants had to judge the changes of the emotional state of the stories protagonist in the presence or absence of EFE. After quality control, 21 data sets entered the final analyses. The presence of EFE during affective ToM judgments was associated with shorter reaction times as well as increased activation of the right amygdala, most probably located in the basolateral nucleus (BLA), coincident with reduced activation of ToM-related regions of the prefrontal cortex. Psychophysiological interactions (PPI) revealed EFE-dependent modulation of connectivity between the right BLA and the contralateral ToM network regions. In combination with the functional interaction of EFE and affective ToM in the right amygdala, our data suggest a complementary but parallel organization of EFE processing and affective ToM. In this framework, the amygdala seems to act as an EFE detector when affective ToM judgments are demanded. Additionally, the facts that EFE induced exclusively right-sided amygdala activation and modulated the connectivity with the contralateral ToM network support the idea of a functional lateralization of stimulus driven components of affective ToM.